Cephalometric Evaluation of Pharyngeal Airway Space among Different Skeletal Malocclusions in United Arab Emirates Residents: A Cross-Sectional Study - Jensyll Rodrigues; Ab Rani Samsudin; Ahmed Ismail; Saad Al Bayatti; Snigdha Pattanaik; Vinayak Kamath; Vellore Kannan Gopinath; Yazan Mahmoud; Shishir Ram Shetty (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To determine the relationship between skeletal malocclusion and upper pharyngeal airway space in the United Arab Emirates population using linear cephalometric measurements. Material and Methods: A retrospective cross-sectional study was performed on lateral cephalogram radiographs acquired from the University Dental Hospital. Through convenience sampling, 70 lateral cephalograms were selected from 200, meeting the inclusion criteria for this study. Study subjects were divided into three groups: Class I (n=25), Class II (n=21), and Class III (n=24). The study groups were compared based on the linear upper pharyngeal airway space measurements. Results: The three groups observed significant differences between the upper pharyngeal airway measurements. No differences in parameters were noted within the male and female study subjects. A highly significant difference (p<0.001) in the Palatal Pharyngeal Distance was observed among the groups. Similarly, when the mean Middle Pharyngeal Distance and mean Inferior Pharyngeal Distance were compared among the three study groups, a highly significant difference (p<0.001 and p<0.004, respectively) was observed. Conclusion: The highest variation in the linear dimensions of the upper pharyngeal airway space among the different skeletal malocclusion was observed in the Nasopharynx, Skeletal Class III having the most prominent dimensions followed by Class I and the least in Class II skeletal malocclusion.